2015
DOI: 10.1177/0954406215592921
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the fault diagnosis of typical faults in reciprocating compressor valves

Abstract: The failure of suction/discharge valves is the most common cause of unscheduled compressor shutdowns; therefore, the in-time fault diagnosis of valves is crucial to the reliable operation of reciprocating compressors. Major valve faults include leakage, valve flutter, delayed closing, and improper lift. To determine the features for diagnosing these typical valve faults, this paper presents an experimental study of the fault diagnosis of reciprocating compressor valves with acoustic emission technology and sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…35,53,54 This is further supported by the results from Wang et al. 55,56 that the burst AE signals coincide exactly with the valve opening and closing timing measured by the displacement sensor. However, although the authors stated that increasing discharge pressure can cause a delay in suction valve opening (SVO) and discharge valve closing (DVC), detailed relationship between discharge pressure and AE amplitude is not examined.…”
Section: Introductionmentioning
confidence: 58%
“…35,53,54 This is further supported by the results from Wang et al. 55,56 that the burst AE signals coincide exactly with the valve opening and closing timing measured by the displacement sensor. However, although the authors stated that increasing discharge pressure can cause a delay in suction valve opening (SVO) and discharge valve closing (DVC), detailed relationship between discharge pressure and AE amplitude is not examined.…”
Section: Introductionmentioning
confidence: 58%
“…Sensors that are often employed for this function include eddy current displacement (ECD), inductive (magnetic), and optical transducers. 32,33…”
Section: Rotaing Machinery Faults and Conventional Monitoring Methodsmentioning
confidence: 99%
“…4 (2021) divided equally into a training and testing samples. In reference [11], the simulated motion of the suction and discharge valves as well as the measured AE signals are studied for the purpose of the fault diagnosis of valves in air compressors. It was found in the study that the valve fault can be identified as an increase in the AE amplitude.…”
Section: Introductionmentioning
confidence: 99%